Persepsi tentang Banjir dan Partisipasi Warga dalam Strategi Mitigasi Bencana pada Komunitas Rawan Banjir - Primadhani, Heradhyta Amalia; Panjaitan, Nurmala K (Jurnal Sains Komunikasi dan Pengembangan Masyarakat [JSKPM], 2020)
Disasters can damage and cause harm from various aspects of life. Every individual can prevent disasters with disaster prevention measures. The actions taken are influenced by the perception of disaster. Perception is an element that supports citizen participation in disaster prevention efforts. The purpose of this study are to identify and analyze perceptions about disasters and citizen participation in disaster mitigation strategies. This study uses a quantitative approach with survey methods and is supported by qualitative data through in-depth interviews and observations. The number of samples chosen using incidental techniques amounted to 45 respondents. The selection of informants is done intentionally. The results showed that individual characteristics were not significantly related to the perception of disaster. Communities that perceive disasters well, make the community increasingly involved in disaster mitigation strategies but in carrying out personal responsibilities are less involved.Keywords: disaster, mitigation, participation, perception